Correlation between ball speed of the spike and the strength condition of a professional women's volleyball team during the season - Valadés, D.; Palao, J. M.; Aúnsolo, Á.; Ureña, A. (Kinesiology, 2016)
The aim of this paper was to study the relationship between spike speed and the players` characteristics, anthropometrics, and strength levels throughout the season for a women`s professional volleyball team. Players from a Spanish first division team performed a battery of tests evaluating anthropometric characteristics, strength performance, and spike speed at the beginning, in the middle, and at the end of one competitive season. The variables were: age; training experience; height; one-hand standing reach height; body mass; ody mass index; height of the vertical jump with an approach (spike jump); muscle percentage of arms; 1 repetition maximum (1RM) bench press; 1RM pullover; overhead medicine ball throws for distance using 1, 2, 3, 4, and 5 kg; spike angles; and speed of standing and jump spikes. Results showed that players` general strength (bench press and pullover) and power parameters (medicine ball throws) increased throughout theseason, while speed of the jump did not improve. The variable that best predicted the jump spike speed at all the three time points in the season was the standing spike speed. The players` training increased their strength and upper-body power, but these improvements were not transferred to players` hitting speed ability. Push-pull and throwing exercises were not specific enough to improve the hitting ability of the female senior volleyball players.